2022
DOI: 10.1021/acsanm.2c01413
|View full text |Cite
|
Sign up to set email alerts
|

FeOCl Nanoparticles Loaded onto Oxygen-Enriched Carbon Nanotubes and Nickel-Foam-Based Cathodes for the Electro-Fenton Degradation of Pollutants

Abstract: Electrochemical advanced oxidation processes (EAOPs) are a class of promising technologies for wastewater remediation. The challenge of EAOPs is the in situ generation and activation of hydrogen peroxide (H2O2) to evolve reactive oxygen species (ROS) simultaneously with low energy consumption and high performances. In this work, we designed an EAOP system, coupling FeOCl nanoparticles on oxygen-enriched carbon nanotubes (O-CNTs) and a nickel foam (FeOCl/O-CNTs/NF) cathode for electro-Fenton (EF) reactions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…14−17 However, their catalytic activity cannot meet with practical application due to the low reduction rate of Fe 3+ /Fe 2+ by H 2 O 2 where the rate-limiting step and key issue in Fenton reactions is. 18,19 Thus, many strategies are proposed and investigated to accelerate H 2 O 2 decomposition and the Fe 3+ /Fe 2+ cycle. 20 Previous studies have demonstrated that oxygen vacancies (OVs) show great potential in certain metaloxide-based Fenton systems attributed to the influence of electron structures, charge transport, and surface properties on the catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14−17 However, their catalytic activity cannot meet with practical application due to the low reduction rate of Fe 3+ /Fe 2+ by H 2 O 2 where the rate-limiting step and key issue in Fenton reactions is. 18,19 Thus, many strategies are proposed and investigated to accelerate H 2 O 2 decomposition and the Fe 3+ /Fe 2+ cycle. 20 Previous studies have demonstrated that oxygen vacancies (OVs) show great potential in certain metaloxide-based Fenton systems attributed to the influence of electron structures, charge transport, and surface properties on the catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they have received growing attention for their multifunctionalization in various applications . The weak ferromagnetism, ferroelectricity, and various catalytic properties of bismuth ferrites were reported in favor of the wide application in ferroelectric memory, information storage, sensors, and environmental purification. However, their catalytic activity cannot meet with practical application due to the low reduction rate of Fe 3+ /Fe 2+ by H 2 O 2 where the rate-limiting step and key issue in Fenton reactions is. , Thus, many strategies are proposed and investigated to accelerate H 2 O 2 decomposition and the Fe 3+ /Fe 2+ cycle . Previous studies have demonstrated that oxygen vacancies (OVs) show great potential in certain metal-oxide-based Fenton systems attributed to the influence of electron structures, charge transport, and surface properties on the catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…Herein, an efficient and robust strategy is proposed for assembling reduced graphene oxide-encapsulated iron oxychloride-integrated carbon cloth (FeOCl/CC@rGO) composite cathodes with a well-controlled hierarchical structure via electrophoretic deposition (EPD). FeOCl was selected as the catalyst due to its excellent activity for H 2 O 2 decomposition, and the performance of the prepared cathode was assessed in terms of its service life and reactivity. Furthermore, by integrating control experiments and density functional theory (DFT) calculations, the structure–property relationship and electron modulation mechanism of this chainmail catalysis in catalytic heterogeneous EF activation were determined.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, in a multidisciplinary collaboration between universities and institutions from South Australia, including the University of South Australia and the University of Adelaide, the authors utilized hydrothermal etching to engineer spikelike nanostructures on titanium substrates for the treatment of anaerobic dental pathogens . In another work led by the University of Adelaide, Zhong et al developed cathodes based on FeOCl nanoparticles decorated on oxygen-enriched carbon nanotubes for the electro-Fenton degradation of pollutants …”
mentioning
confidence: 99%
“…7 In another work led by the University of Adelaide, Zhong et al developed cathodes based on FeOCl nanoparticles decorated on oxygen-enriched carbon nanotubes for the electro-Fenton degradation of pollutants. 8 Two of the Australian research groups in the forum used nanomaterials to generate high-efficiency optical devices with enhanced properties. Here, Gunenthiran et al from the University of Adelaide engineered nanoporous anodized alumina for developing photonic crystals.…”
mentioning
confidence: 99%